Assessing fire hazard in coastal heathlands: Predicted impacts of weather, land use and management - Bente Halvorsen; Kristine M. Grimsrud (Statistics Norway, Research Department, 2024)
Unmanaged and overgrown coastal heathlands represent a substantial fire hazard. We analyse how this hazard in Norwegian coastal heathlands is influenced by weather conditions, land management, and usage. Our analysis integrates vegetation, maintenance, and management data with emergency response records from fire departments and weather data. Using panel data regressions, we assess the risk of fire in response to these variables. A key finding is that increased coastal heathland management significantly reduces fire risk, particularly during droughts, warm weather, and periods with strong winds. The reason is that well-maintained coastal heathlands having reduced levels of dry vegetation, making them less susceptible to ignition even during conditions when the overall fire hazard is increased.
Keywords: C23; Q15; Q54; Q57; 330; Land use; Landscape maintenance; Costal heathlands; Fire hazard; Panel data